1994
DOI: 10.1128/jb.176.5.1309-1315.1994
|View full text |Cite
|
Sign up to set email alerts
|

A distant upstream site involved in the negative regulation of the Escherichia coli ompF gene

Abstract: The two-component regulatory system, OmpR-EnvZ, of Escherichia coli K-12 regulates the expression of the major outer membrane porin protein, OmpF. OmpR is a DNA-binding protein which acts as both an activator and a repressor to control ompF transcription. In this article, we describe a new OmpR-binding site that is located between 384 to 351 bp upstream from the ompF start point of transcription. Inactivation of this site by insertion of a 22-bp fragment prevents the repression of ompF expression conferred by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 52 publications
(27 reference statements)
4
59
0
Order By: Relevance
“…Finally, it seems likely that the stimulatory effect of phosphorylation on cooperative interactions could also be used to explain ompF repression under high osmolarity conditions. Previous studies have suggested that the repression of ompF transcription involves the formation of a DNA loop (8,18,19). One intriguing possibility is that the stimulation of cooperative interaction by high cellular levels of OmpR-P could result in the occupancy of the F3 and F4 sites.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it seems likely that the stimulatory effect of phosphorylation on cooperative interactions could also be used to explain ompF repression under high osmolarity conditions. Previous studies have suggested that the repression of ompF transcription involves the formation of a DNA loop (8,18,19). One intriguing possibility is that the stimulation of cooperative interaction by high cellular levels of OmpR-P could result in the occupancy of the F3 and F4 sites.…”
Section: Discussionmentioning
confidence: 99%
“…38 It has been reported that the difference in OmpF expression between the E. coli BL21(DE3) and K12 strain might be explained by two mutations at positions -18 and -363 in the ompF promoter and its upstream region. Position -363 is within the OmpR binding site, 39 so the mutation seems to affect OmpR binding, and thus the repression of ompF expression. We have prepared a BL21(DE3) ompF knock-out strain for protein expression for a future comparison study.…”
Section: Crystal Packing Of Ompf Prepared In Fc12mentioning
confidence: 99%
“…Purified GST-Tas was incubated with 32P-end labeled oligonucleotides or DNA fragments in a binding buffer (10 mM Tris-Cl (pH 7.5)/65 mM KCl/2.5 mM MgCI2/l mM dithiothreitol/5% glycerol) con- Footprinting by the DNase I Protection Method. The DNase I protection assay for identifying nucleotides in viral target elements binding Tas was done as described (18,20). Briefly, probes were prepared by digesting the plasmid pMl (see Fig.…”
Section: Methodsmentioning
confidence: 99%